Analysis of Register Used in Reader’s Digest Magazine’s Food Columns - Sungkawati Kardi Wahyuningsih (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2021)
This research is qualitative applying content analysis. The objectives of this research are to describe the types of register, and to describe the meanings of register based on the Reader’s Digest magazine’s food columns. The source of the data in this research was the food columns in Reader’s Digest magazines. Technique of data collection was carried out by reading and taking note. The main instrument of this research was the researcher herself while the secondary instruments were data sheets. The trustworthiness of the data analysis was achieved with the employment triangulation technique. The research findings show 138 register items. The results reveal that the forms of register found in this research are the oratorical frozen register (12.3%), the deliberative/formal register (60.2%), the consultative register (11.6%), the casual register (12.3%), and the intimate register (3.6%). Of the five types of register, the deliberative/formal register ranks first. This means that the writer honors the reader beside the intimacy between them.